2016
DOI: 10.1073/pnas.1523357113
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of auditory attention synchronize with speech

Abstract: Attention plays a fundamental role in selectively processing stimuli in our environment despite distraction. Spatial attention induces increasing and decreasing power of neural alpha oscillations (8-12 Hz) in brain regions ipsilateral and contralateral to the locus of attention, respectively. This study tested whether the hemispheric lateralization of alpha power codes not just the spatial location but also the temporal structure of the stimulus. Participants attended to spoken digits presented to one ear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
234
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(273 citation statements)
references
References 60 publications
31
234
7
1
Order By: Relevance
“…First, electrophysiological studies of selective attention have demonstrated that auditory tasks can modulate posterior alpha (Foxe et al, 1998; Wöstmann et al, 2016), as was observed in our data. Furthermore, alpha activity has been theorized as a gating mechanism of task-irrelevant information (Jensen and Mazaheri, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…First, electrophysiological studies of selective attention have demonstrated that auditory tasks can modulate posterior alpha (Foxe et al, 1998; Wöstmann et al, 2016), as was observed in our data. Furthermore, alpha activity has been theorized as a gating mechanism of task-irrelevant information (Jensen and Mazaheri, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies in the auditory domain had localized the origin of the low-frequency activity to sensory areas and not frontal regions (13,14,35) but were confounded by the presentation rate, which likely evoked activity (14,35,36). Given that exogenous stimulation induces a strong phase alignment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that lowfrequency neuronal oscillations might reflect a cortical mechanism for sensory selection, attentional allocation, and evidence updating during decision making (9,11,13,14,32). If the underlying functional brain architecture is inherently rhythmic, then we should be able to observe rhythmic patterns in behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence of lateralized alpha-power increases in ACs ipsilateral to the attended ear (Müller and Weisz, 2012). However, only a few previous studies have been able to show a direct relationship between AC alpha oscillations and distracter-elicited neuronal responses (Wöstmann et al, 2016). The alpha inhibition hypothesis is contrasted by an alternative interpretation that alpha synchronization enhances stimulus maintenance at the network level (Leiberg et al, 2006; Obleser et al, 2012; Palva and Palva, 2007; Wilsch and Obleser, 2015).…”
Section: Introductionmentioning
confidence: 99%